MANAGEMENT OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE IN IMPROVING THE LEARNING PROCESS AT RAUDHATUL ULUM SAKATIGA INTEGRATED ISLAMIC HIGH SCHOOL - Oviyanti, Fitri; Maryamah, Maryamah; Rahayu, Meiliza Suci; Selviana, Lista (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to describe the types of facilities and infrastructure contained in the Integrated Islamic High School Raudhatul Ulum Sakatiga, as well as the management of school facilities and infrastructure in improving the quality of learning at school. This type of research is Descriptive Qualitative research where this research uses books, journals and several interviews with sources as research materials. The findings of this study are that there are still facilities and infrastructure at Raudhatul Ulum Integrated Islamic High School that are not yet adequate as described, school facilities that are still often hampered are the availability of stationery in the classroom in the office, management of cleaning tools in the classroom and in the office. but the school as much as possible procures facilities and infrastructure needed by students and teachers and repairs infrastructure that requires repair in order to take place effective and efficient learning.